2002
DOI: 10.1088/0953-8984/14/48/384
|View full text |Cite
|
Sign up to set email alerts
|

Free carrier mobility in AlGaN/GaN quantum wells

Abstract: Experimental results show that the free carrier mobility in AlGaN/GaN quantum wells strongly decreases with the carrier density. Using the dynamical theory, we show that this behaviour can be explained by a combination of phonon, carrier-carrier and interface defect scattering mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For even higher AlGaN thickness (54 nm, not shown) no 2DEG could be detected. The strong mobility decay for high carrier density has recently been theoretically attributed to an increase of "interface-roughness-like" scattering mechanism [7]. The question that arises then is what is this "interface-like" scattering potential?…”
Section: Relaxation In Algan Thin Layersmentioning
confidence: 99%
“…For even higher AlGaN thickness (54 nm, not shown) no 2DEG could be detected. The strong mobility decay for high carrier density has recently been theoretically attributed to an increase of "interface-roughness-like" scattering mechanism [7]. The question that arises then is what is this "interface-like" scattering potential?…”
Section: Relaxation In Algan Thin Layersmentioning
confidence: 99%
“…In contrast, the low-temperature mobility is rather controlled by electron scattering related to the background ionized impurities, charged dislocation cores, small-scale interface roughness, and alloy disorder in the AlGaN cap layers [1][2][3][4][5]. Two former mechanisms dominate at the 2DEG concentration n less than ∼ 10 12 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Scattering by optical phonons is the principal mechanism limiting the room-temperature mobility of two-dimensional electron gas (2DEG) in AlGaN/GaN high-electron mobility transistor (HEMT) heterostructures (see, for instance, [1]). In contrast, the low-temperature mobility is rather controlled by electron scattering related to the background ionized impurities, charged dislocation cores, small-scale interface roughness, and alloy disorder in the AlGaN cap layers [1][2][3][4][5]. Two former mechanisms dominate at the 2DEG concentration n less than ∼ 10 12 cm −2 .…”
mentioning
confidence: 99%
“…AlGaN/GaN heterostructures possess attractive electronic and mechanical properties, which make them interesting for being implemented in the production of devices capable of high performance and able to work in hostile environments. One of their most unusual features is the presence, at the AlGaN/GaN interface, of a two-dimensional electron gas (2DEG) with carrier densities n s as high as 10 13 cm −2 , even in nominally 1 Present address: Institut d'Electronique Fondamentale, Université Paris Sud, Bât. 220-Centre scientifique d'Orsay, 91405 Orsay, France.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of experimental and theoretical work is devoted to the understanding of the electronic properties of this quantum well, but also to the characterization of the interface defects and to the understanding of the way they may interact with the electrons limiting their 2D mobility. In some of the authors' previous studies about transport in AlGaN/GaN quantum wells [1,2], the effect of the interface defects (like misfit dislocations, surface cracks, alloy reordering etc), originated by the relaxation of the strain energy accumulated in the AlGaN top layer, was referred to as 'interface electrical roughness', because of the non-uniform charge distribution induced by such defects at the interface. The results showed that this scattering mechanism contributes to the room temperature mobility drop at high electron concentration.…”
Section: Introductionmentioning
confidence: 99%